Numerical study on the influence of flexible net permeability on debris flow impact loads. - Yanfen Wang; Siyu Xiao; Linbo Qiao (PLoS ONE)
Debris flows in mountainous regions pose a significant threat to human lives and property. Flexible protection nets are widely used in debris flow prevention projects; however, their effectiveness requires improvement. This study integrates field investigations, DEM simulations, and numerical analyses to comprehensively explore the impact of flexible net permeability on debris flow dynamics. The results indicate that debris flow particle size significantly affects impact velocity, with larger particles exhibiting higher velocities. Different accumulation patterns also lead to distinct velocity distributions. Regarding the tensile forces in the flexible net's support ropes, the lower ropes bear greater loads, and these forces increase as debris flow particle size grows. Debris flow accumulation height is influenced by particle size and deposition patterns; excessive heights can damage the nets. Small debris flows cause minimal net deformation, while large debris flows result in more substantial deformation due to full interception. These findings provide critical insights for optimizing flexible net design in debris flow protection, guiding parameter selection and structural enhancements. Additionally, they inform the development of more effective prevention strategies, ultimately reducing disaster-related losses.